A 3D Biocompatible Plasmonic Tweezer for Single Cell Manipulation. Issue 2 (8th January 2023) - Kang, Siyu; Nisar, Muhammad Shemyal; Lu, Yu; Chang, Ning; Huang, Yan; Ni, Haibin; Novikov, Sergey M.; Wang, Yi; Cui, Qiannan; Zhao, Xiangwei
Abstract: Plasmonic tweezers are an emerging research topic because of their low input power and wide operating range from homogeneous particles to complex biological objects. But it is still challenging for plasmonic tweezers to trap or manipulate objects of tens of microns, especially in biological science. This study introduces a new 3D biocompatible plasmonic tweezer for single living cell manipulation in solution. The key design is a tapered tip whose three‐layer surface structure consists of nanoprobe, gold nanofilm, and thermosensitive hydrogel, thiolated poly( N ‐isopropylacrylamide). Incident light excites the surface plasmon polaritons on gold film and generates heat to induce thermally driven phase transition of the thermosensitive hydrogel, which enables reversible binding between functionalized surface and cell membrane and avoids both thermal and mechanical stresses in the meanwhile. The 3D biocompatible plasmonic tweezer realizes selective capture, 3D pathway free transport, and position‐controlled release of target cells, and it displays excellent biocompatibility, low energy consumption, and high operational flexibility. Abstract : The biocompatible photothermal fiber tweezer cleverly combines the surface plasmons‐mediated photothermal effect of gold nanofilm with thermally induced phase transition of thermosensitive hydrogel, enabling manipulation of single living cells in solution through reversible binding of functionalized surface and cell membrane. An input power as low as 900 µW can be used to realize single‐cell capture within 20 s.